Estrategia metodológica para fomentar la inteligencia interpersonal en los docentes de bachillerato de la unidad educativa “Antonio José de Sucre” del cantón Santa Rosa, provincia El Oro, en el año 2013. - Macas, María Merecedes (2015)
Importantly permanent failures, irregularities and inconsistencies in the educational aspect in the implementation of education by the authority, principals and teachers This has allowed for the author of this study focus the research project one of the problems and troubling aspects of contemporary education the selected schools the Antonio José de Sucre Education Unit Citadel Palms City Santa Rosa province of El Oro, where the author works as a teacher.